Molecular dynamics simulation on the mechanical properties of Zr-Cu metallic nanoglasses with heterogeneous chemical compositions - Li, Tian; Li, Nana; Kuang, Bo; Zheng, Guangping (Frontiers in Materials, 2024)
The mechanical properties of metallic nanoglasses (NGs) strongly depend on the average size of glassy grains (Davg). Nevertheless, current knowledge on the effects of sizes of glassy grains is incomplete for the mechanical properties of NGs. Herein, ZrxCu100-x (25≤x≤75) nanoglasses containing glassy grains with different chemical compositions, i.e., the heterogeneous NGs (HNGs), are investigated by molecular dynamics simulation, and the relation between ultimate tensile strength (UTS) and Davg is determined. Specifically, the UTS decreases with decreasing Davg in Zr-Cu HNGs when Davg<10 nm, mainly resulting from the increased volume fraction of glass-glass interfaces, while UTS would follow the Hall-Petch like relation for Zr-Cu HNGs when Davg>10 nm, which is closely related to glassy grains with compositions dominated by Zr atoms. This study provides a deep insight into the mechanical property dependence on grain size in the HNGs, which could be a novel strategy in resolving the issue of strength-ductility tradeoff in NGs.